The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/10826084.2013.824468
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Among Adolescents in California: A Latent Class Analysis

Abstract: Data from the California Healthy Kids Survey of 7th, 9th, and 11th graders were used to identify latent classes/clusters of alcohol, tobacco, and marijuana use (N=418,702). Analyses revealed four latent classes of substance use which included non-users (61.1%), alcohol experimenters (some recent alcohol use; 22.8%), mild poly-substance users (lifetime use of all substances with less than three days of recent use; 9.2%), and frequent poly-substance users (used all substances three or more times in the past mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 31 publications
(41 reference statements)
1
23
1
1
Order By: Relevance
“…We found that Hispanic and Asian youth were less likely to be concurrent users of some typologies than White adolescents (A+C and A+M+C) and null effects for the other typologies (A+M, M+C). These findings contradict previous research suggesting that Hispanic youth are at higher risk for concurrent use than their White peers (Connell et al, 2009; Gilreath et al, 2014; Gilreath et al, 2015), as well as research suggesting Asian youth are at lower risk for A+M and M+C than Whites and other racial/ethnic groups (Lanza et al, 2010; Ramo et al, 2012). Native American youth were found not to differ from Whites on use of any concurrent substance-use typology.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We found that Hispanic and Asian youth were less likely to be concurrent users of some typologies than White adolescents (A+C and A+M+C) and null effects for the other typologies (A+M, M+C). These findings contradict previous research suggesting that Hispanic youth are at higher risk for concurrent use than their White peers (Connell et al, 2009; Gilreath et al, 2014; Gilreath et al, 2015), as well as research suggesting Asian youth are at lower risk for A+M and M+C than Whites and other racial/ethnic groups (Lanza et al, 2010; Ramo et al, 2012). Native American youth were found not to differ from Whites on use of any concurrent substance-use typology.…”
Section: Discussioncontrasting
confidence: 99%
“…In general, male adolescents report higher rates of daily alcohol, marijuana, and cigarette use than female adolescents (Lanza et al, 2015; Miech et al, 2016). As for concurrent use, the most consistent sex effect has been found for occasional concurrent users (i.e., lifetime users of alcohol, marijuana and cigarettes, with little recent concurrent use), who are more likely to be female than male (Connell et al, 2010; Gilreath et al, 2014; Gilreath et al, 2015). However, findings have been mixed regarding sex differences in the frequent/recent use of alcohol, marijuana and cigarettes.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…20 On the other hand, it may represent a standard, welldocumented class of polysubstance users who have simply extended their use of drugs to a new device. [21][22][23] Furthermore, the heightened use of nicotine in this group warrants future analysis to examine whether their level of nicotine inhaled reaches that of their peers who use cigarettes. A third limitation is that the study lacks information on youth who have vaped multiple, different substances within the past 30 days.…”
Section: Discussionmentioning
confidence: 99%